STRATEGI PENGEMBANGAN CINDERAMATA BELERANG WISATA KAWAH IJEN BANYUWANGI - Adetiya Prananda Putra; Halil Halil; Nizha Pratiwi (Universitas Merdeka Malang, 2019)
Ijen crater destination is one of the favorite of tourism object in Banyuwangi. Ijen crater has the interesting tourism that is lake crater that contains sulfur with the exotic of the blue fire, the unique of traditional miners, also the kind of flora and fauna. Moreover, ijen crater destination has superior product that is souvenir of sulfur that needed strategy to develop the existence of the product to get costumer satisfaction. The purposes of this research to know the development strategy souvenirs of sulfur in ijen crater destination Banyuwangi District and to know the development priority strategy souvenir of sulfur in ijen crater destination Banyuwangi District. As for, data analysis technique using Internal Factor Evaluation (IFE), External Factor evaluation (EFE), Matrix Internal External (IE, Strengths, Weaknesses, Opportunities, an Threats (SWOT), and Analytical Hierarchy Process (AHP) to determine the development strategy souvenir of sulfur. The result of this research that is the priority strategies that can recommendation to develop souvenirs of sulfur that are (1) the government gives facilities and infrastructures to do intensive promotion activities, (2) to create be kind of the interesting product, (3) coordination that intensive with stakeholder to improvement sustainable development, (4) to establish cooperation with the managers of mining as team work to sustainable development, (5) to do training for the souvenirs of sulfur craftsman by the government, (6)to increase the quality of product that more creative.